Fantasia - Stokowski, Leopold, 1882-1977.; Taylor, Deems, 1885-1966.; Bach, Johann Sebastian, 1685-1750.; Tchaikovsky, Peter Ilich, 1840-1893.; Dukas, Paul, 1865-1935.; Stravinsky, Igor, 1882-1971.; Beethoven, Ludwig van, 1770-1827.; Ponchielli, Amilcare, 1834-1886.; Mussorgsky, Modest Petrovich, 1839-1881.; Schubert, Franz, 1797-1828.; Philadelphia Orchestra; Walt Disney Pictures; et al. (Burbank, Calif. : Walt Disney Home Video : Distributed by Buena Vista Home Video, 1991)
An extraordinary blend of magnificent music and classic Disney animation, featuring a host of unforgettable images, including Mickey Mouse as The Sorcerer's apprentice.
Toccata and fugue in D minor / J.S. Bach -- The nutcracker suite / P.I. Tchaikovsky -- The sorcerer's apprentice / P. Dukas -- Rite of spring / I. Stravinsky -- The Pastoral symphony (The sixth) / L. Beethoven -- Dance of the hours / A. Ponchielli -- Night on Bald Mountain / M. Moussorgsky -- Ave Maria / F. Schubert.
A restored version of the original motion picture.
Rated G.
Closed-captioned.
Production supervisor, Ben Sharpsteen ; story direction, Joe Grant, Dick Huemer ; musical direction, Edward H. Plumb ; musical film editor, Stephen Csillag ; recording, William E. Garity, C.O. Slyfield, J.N.A. Hawkins ; narrator, Deems Taylor.
Philadelphia Orchestra ; Leopold Stokowski, conductor.
VHS; stereo, digitally mastered; Dolby surround.
Keywords: Video recordings for the hearing impaired; Feature films; Animated films